Individual Differences in Perceptions of Social Presence: Exploring the Role of Personality in Online Distance Learning - Weidlich Joshua; Kreijns Karel; Bastiaens Theo J. (De Gruyter, 2021)
Social presence is a central concept relating to interpersonal aspects in online distance learning. However, the conditions and determinants of its emergence are not yet fully understood. As a construct rooted in social psychology, the potential of individual differences predicting perceptions of social presence has been largely neglected, thus, constituting a gap in our understanding. In a sample of 201 online distance education students, the merits of a trait-level view of social presence were investigated. To this end, personality was assessed using the Big Five personality inventory, exploring both a dimensional and a typological approach. Results suggest that specific personality typologies may be more prone to perceptions of social presence, thus calling for an extension of our theoretical modeling of the construct.